Consumption of Young Coconut Water as an Effort to Treat Menstrual Pain in Adolescent Girls - Lia, Hasrita Octaliana; Purda Listya, Endah; Susanti, ⁠Nurul Fatimah; Herlisah, Herlisah (Universitas Islam Jember, 2024)
Some women experience pain and cramps during menstruation. The pain usually occurs in the lower abdomen. One non-pharmacological effort can be done by consuming young coconut water, which contains folic acid as a component in producing red blood cells. Sufficient blood production will facilitate blood circulation so that the cells meet their oxygen and nutritional needs. With this condition, the body will be more resistant to the sensation of menstrual pain caused during menstruation. The method uses a pre-experimental research design with a one-group pretest-posttest design. Data were collected using a numeric rating scale (NRS) observation sheet to assess the menstrual pain scale. Data were analyzed using univariable and bivariable analysis with the Wilcoxon statistical test. The research results, based on statistical test results for menstrual pain before giving young coconut water, had an average of 3.53, and after giving young coconut water, an average of 1.18. The Wilcoxon test obtained a significant value of ρ= 0.000 (<0.05). The conclusion of this research is that there is an effect of giving young coconut water on menstrual pain in young women in Pemusiran Village, Sungai Tering Health Center Working Area in 2024.